2021
DOI: 10.11648/j.ejcbs.20210703.12
|View full text |Cite
|
Sign up to set email alerts
|

Latrine Utilization and Associated Factors Among Households in SebetaHawas Woreda, Oromia Special Zone, Ethiopia

Abstract: In developing regions almost half of the population does not have access to improved latrine facilities. In Ethiopia up to 60% of the current disease burden was attributable to poor sanitation. However, the information regarding latrine utilization was minimal in the study area. This study assessed the magnitude of latrine utilization and associated factors among households in SebetaHawas Woreda Oromia special zone, Ethiopia from June 1-20, 2019. Cross-sectional study design was conducted. Using interviewer ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 10 publications
3
9
2
Order By: Relevance
“…Household heads who were able to write and read used their latrine about 3.86 times more likely than their counterparts. Similar results were reported from the studies conducted in SebetaHawas Woreda [ 23 ], Laelai Maichew Woreda [ 42 ], Chencha [ 26 ], and Gurage zone [ 46 ]. This is explained by the fact that education can increase the knowledge about the diseases related to improper disposal of human wastes and lead to changes in latrine utilization behavior [ 22 ].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Household heads who were able to write and read used their latrine about 3.86 times more likely than their counterparts. Similar results were reported from the studies conducted in SebetaHawas Woreda [ 23 ], Laelai Maichew Woreda [ 42 ], Chencha [ 26 ], and Gurage zone [ 46 ]. This is explained by the fact that education can increase the knowledge about the diseases related to improper disposal of human wastes and lead to changes in latrine utilization behavior [ 22 ].…”
Section: Discussionsupporting
confidence: 87%
“…The overall latrine utilization prevalence in our study is lower than the reports of latrine utilization in Sebeta Hawas-68% [ 23 ], Mehal Meda town-90% [ 24 ], semi-urban areas of North Eastern Ethiopia-71.8% [ 37 ], Denbia district-86.8% [ 25 ], Aneded district-63% [ 44 ], Hulet Ejju Enessie Woreda-60.7% [ 41 ], Chencha district-60% [ 26 ], Wondo Genet district, South Ethiopia-83.1% [ 45 ], and Hawassa town [ 38 ]. The latrine utilization among CLTSH-implemented villages in this study was also lower than the one in Gurage Zone’s Community-Led Total Sanitation and Hygiene implemented kebeles-65.8% [ 46 ].…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…The magnitude of latrine utilization in the study area (67.1%) was consistent with the study done in Gurage Zone, Ethiopia (65.8%) and Sebeta district, Oromia, Ethiopia (68%). 23,26 But it was higher than the study done in Takusa district, Northwest, Ethiopia (41.9%), East Gojjam zone (45.4%), and the study done at Tullo district, Eastern Ethiopia (56.1%). 27,28 Reason might be different in operational definition of the outcome variable, difference in the study period and study design.…”
Section: Discussionmentioning
confidence: 60%
“…A structured questionnaire and observational checklist was developed after reviewing relevant literatures. 13 , 14 , 16 , 20 , 22 , 23 The questions to assess psychosocial variables was adapted from RANAS, and from a other behavioral studies that applied the same model by which its applicability was confirmed in many previous studies. 16 , 24 , 25 Then 6 diploma data collectors (1 Environmental health and 5 Nurses) who have smart (android) phone, were collect the data by face to face with household head or housewife using a prepared tool by Open data kit (ODK) data collect, and latrine utilization was verified through observation of at least 2 signs from sign of latrine use.…”
Section: Methodsmentioning
confidence: 99%